Faktor-Faktor Yang Mempengaruhi Kepuasan Pengguna Sistem Informasi Manajemen Rumah Sakit (SIMRS) Rawat Inap di RSUD Dr Moewardi - Wulandari, Dewi Septiana; Sutrisno, Trismianto Asmo; Sugiarsi, Sri (Politeknik Negeri Jember, 2024)
The Hospital Management Information System (called SIMRS) is an application used for managing all medical record data in hospitals. In the implementation of the SIMRS for inpatient services at Dr. Moewardi Hospital, there are still variables that need improvement, such as poor layout, inadequate color composition, and incomplete information. The aim of this research was to determine the factors that influence the satisfaction of inpatient SIMRS users. The research design was an observational analytic study with a cross-sectional approach. The study population consisted of all 1,843 users of the inpatient SIMRS, with a sample size of 106 respondents. Data collection was conducted using a questionnaire, and data analysis was performed using multiple linear regression tests. The study results showed that the variables of content, accuracy, and timeliness have a partial influence on user satisfaction, while the variables of format and ease of use do not. Additionally, there was a simultaneous influence of the variables content, accuracy, format, ease of use, and timeliness on user satisfaction. The study suggests that periodic evaluation and improvement of the HMIS should be carried out to achieve optimal user satisfaction